2023
DOI: 10.3389/fneur.2023.1102496
|View full text |Cite
|
Sign up to set email alerts
|

Combined open revascularization and endovascular treatment of complex intracranial aneurysms: case series

Abstract: Background and purposeThe treatment of complex intracranial aneurysms can be challenging with stand-alone open or endovascular techniques, particularly after rupture. A combined open and endovascular strategy can potentially limit the risk of extensive dissections with open-only techniques, and allow for aggressive definitive endovascular treatments with minimized downstream ischemic risk.Materials and methodsRetrospective, single-institution review of consecutive patients undergoing combined open revasculariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…In a similar study that focused on ruptured fusiform aneurysms, treatment-related stroke was observed in 30% of patients. 37) A recent case report of a recurrent large complex middle cerebral artery aneurysm showed that staged hybrid techniques with a superficial temporary artery-M2 bypass, followed by flow-diverter deployment with coil embolization, resulted in complete occlusion without symptomatic complications ( Fig. 2B ).…”
Section: Combination With Evt and Open Surgerymentioning
confidence: 93%
“…In a similar study that focused on ruptured fusiform aneurysms, treatment-related stroke was observed in 30% of patients. 37) A recent case report of a recurrent large complex middle cerebral artery aneurysm showed that staged hybrid techniques with a superficial temporary artery-M2 bypass, followed by flow-diverter deployment with coil embolization, resulted in complete occlusion without symptomatic complications ( Fig. 2B ).…”
Section: Combination With Evt and Open Surgerymentioning
confidence: 93%